Detection and recognition of Bangladeshi fishes using surf features and CNN classifier - Shuhin, Syed Adiba; Tajrin, Jannatul; Akhter, Afrin; Israth, Chowdhury (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.